Type D Personality as a Marker of Poorer Quality of Life and Mood Status Disturbances in Patients with Skin Diseases: A Systematic Review - Manuel Sánchez-Díaz; Trinidad Montero-Vílchez; Maria I. Quiñones-Vico; Álvaro Sierra-Sánchez; Ana Ubago-Rodríguez; Raquel Sanabria-de la Torre; Alejandro Molina-Leyva; Salvador Arias-Santiago (Medical Journals Sweden, 2023)
Type D personality is characterized by social inhibition and negative affectivity. Poorer outcomes and worse quality of life have been linked to type D personality in patients with a variety of non-dermatological diseases. Despite increasing evidence of the importance of type D personality in skin diseases, there are no reviews on this subject. The aim of this review is to summarize the current evidence regarding type D personality and skin diseases. A systematic search was performed using Medline and Web of Science databases from inception to 11 October 2022. Studies addressing the presence of type D personality, its associated factors, its impact on the outcomes of the disease or the quality of life of the patients were included in the systematic review. A total of 20 studies, including 3,124 participants, met the eligibility criteria and were included in the review. Acne, hidradenitis suppurativa, psoriasis, melanoma, atopic dermatitis, chronic spontaneous urticaria and pruritic disorders were the main diseases assessed. Type D personality was more frequent among patients with skin diseases than among controls. Type D personality was found to be associated with poorer quality of life and higher rates of psychological comorbidities in patients with skin diseases. In conclusion, type D personality appears to be a marker of patients with increased risk of poorer quality of life and higher rates of psychological comorbidities. Screening for type D personality in specialized dermatology units might be beneficial to identify patients who are more psychologically vulnerable to the consequences of chronic skin diseases.